Is the Presence of a Depressive Disorder a Risk Factor for Worse Metabolic Outcomes Among Patients with Type 2 Diabetes Treated with GLP-1 Analogs? - Joana Nicolau; Pilar Sanchís; María Isabel Tamayo; Guadalupe Pérez-Bec; Guido Sfondrini; Mireia Grimalt; Lluís Masmiquel (Diabetology)
Background/Objectives: Type 2 diabetes mellitus (T2DM) is frequently associated with depressive disorder (DD), which negatively impacts glycemic control and overall metabolic outcomes. Recent evidence suggests that glucagon-like peptide-1 receptor agonists (GLP-1 RAs) may exert neuroprotective effects and modulate mood. Likewise, it is unknown whether the presence of a DD, due to increased brain inflammation, could lead to a poorer response to GLP-1 RAs in terms of weight loss. This study evaluates the impact of DD on metabolic outcomes in individuals treated with GLP-1 RAs. Methods: We conducted a retrospective longitudinal study including 115 patients with T2DM treated with GLP-1 RAs for at least six months. DD was identified based on a documented clinical diagnosis, chronic antidepressant use, or a Beck Depression Inventory (BDI) score ≥16. Metabolic parameters, including glycated hemoglobin (HbA1c), fasting glucose, the body mass index (BMI), the waist circumference, and triglycerides, were compared between patients with and without DD. Results: Patients with DD had significantly higher baseline HbA1c (7.5% vs. 6.9%, p = 0.01), fasting glucose, and triglyceride levels. The waist circumference was also higher in the DD group (p = 0.001). However, no significant differences were observed in weight loss or BMI reductions following the GLP-1 RA treatment. Final HbA1c levels remained higher in the DD group (7.2% vs. 7.0%, p = 0.01). Conclusions: While DD is associated with a poorer baseline metabolic control in T2DM, it does not appear to impair the weight loss efficacy with GLP-1 RAs. However, patients with DD maintain higher post-treatment HbA1c levels, underscoring the need for integrated metabolic and psychiatric care in diabetes management.